(untitled) (Palíndromo, 2025)
This paper aims to analyze a series of textile exhibitions held between 2021 and 2024 in Latin American art museums, in order to offer insights into their social role. To this end, the analysis proposes a cross-reading of exhibition practices in art museums, drawing from perspectives rooted in museology, decolonial thought, gender studies, memory, and identity. Methodologically, the study adopts an exploratory-descriptive-analytical approach. On one hand, the paper develops readings based on the uniqueness of the exhibited objects — from the realm of the feminine and the revaluation of artisanal knowledge; on the other hand, it analyzes the subjects who articulate the discourses expressed in the narratives of this type of exhibition — museum staff, curators, artists, and artisans/communities. Overall, the article broadens perspectives within the field of study regarding art histories and their gendered, practical, and socio-geographical modulations, through an incursion into the domains of textile creation and exhibition, which represent both artists and communities who, through everyday life and subtle acts of symbolic resistance, sustain this form of practice.